2008
DOI: 10.1016/j.neurobiolaging.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in the neural correlates of force modulation: An fMRI study

Abstract: Functional imaging studies in humans have demonstrated widespread age-related changes in cortical motor networks. However, the relative contribution of cortical regions during motor performance varies not only with age but with task parameters. In this study, we investigated whether motor system activity during a task involving increasingly forceful hand grips was influenced by age. Forty right-handed volunteers underwent functional magnetic brain imaging whilst performing repetitive isometric hand grips with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
164
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 68 publications
20
164
3
Order By: Relevance
“…This area has been shown to be active in motor tasks involving the hand and the foot and in tasks where the recognition of motor pattern is required (Binkofski and Buccino, 2006). This finding that the older adult group displayed greater activation in this area, could indicate an increased amount of processing by premotor circuitry to produce the same force output as the younger group.A common finding in fMRI studies of age related differences in motor control tasks is that older adults show higher levels of bilateral activation of the SMC (Kim et al, 2010;Naccarato et al, 2006;Ward et al, 2008). The present study found that there were no significant age related differences in the activity level of the ipsilateral sensorimotor cortex.…”
supporting
confidence: 46%
See 2 more Smart Citations
“…This area has been shown to be active in motor tasks involving the hand and the foot and in tasks where the recognition of motor pattern is required (Binkofski and Buccino, 2006). This finding that the older adult group displayed greater activation in this area, could indicate an increased amount of processing by premotor circuitry to produce the same force output as the younger group.A common finding in fMRI studies of age related differences in motor control tasks is that older adults show higher levels of bilateral activation of the SMC (Kim et al, 2010;Naccarato et al, 2006;Ward et al, 2008). The present study found that there were no significant age related differences in the activity level of the ipsilateral sensorimotor cortex.…”
supporting
confidence: 46%
“…A number of studies have found a greater reliance on the ipsilateral primary sensorimotor cortex (SMC) in older adults when compared to young adults (Hutchinson et al, 2002;Kim et al, 2010;Mattay et al, 2002;Naccarato et al, 2006;Ward et al, 2008). These tasks have included a paced thumb opposition task (Naccarato et al, 2006), a visually guided gripping task at a moderate force level of approximately 45% of the participants maximum voluntary contraction (MVC) (Ward et al, 2008), a continuous abduction/adduction task with the index finger and a wrist flexion/extension task (Hutchinson et al, 2002) and an elbow flexion and extension task (Kim et al, 2010). Taken together these data suggest that the motor control demands for these tasks require additional neural resources in older adults to achieve the same performance as younger adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous fMRI GF studies focused on the effect of different forces applied using the DH [Keisker et al, 2009; Kuhtz‐Buschbeck et al, 2008; Spraker et al, 2012; Talelli et al, 2008; Ward et al, 2006, 2007, 2008]. In these studies, the regions responded in a linear fashion and were mainly localised with the CL M1 and IL cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the paradigm, an external visually guided cue has been widely used in previous published work [Alahmadi et al, 2015; Galléa et al, 2008; Hilty et al, 2011; Keisker et al, 2009, 2010; Kuhtz‐Buschbeck et al, 2008; Neely et al, 2013; Spraker et al, 2007, 2009, 2012; Sulzer et al 2011; Vaillancourt et al, 2003; Ward, 2004; Ward and Frackowiak, 2003, Ward et al, 2008; Wong et al, 2007]. To underline that such motor paradigms are visually guided, they are often referred to as “visuomotor.”…”
Section: Discussionmentioning
confidence: 99%